PENGARUH PROPRIOSEPTIVE NEUROMUSCULAR FASILITATION STRETCHING DAN BALLISTIC STRETCHING TERHADAP FLEKSIBILITAS OTOT TUNGKAI - Tarmiji Apian; Andika Triansyah; Edi Purnomo (Universitas Tanjungpura, 2019)
AbstractThe problem in this study is whether there is Proprioseptive Neuromuscular Facilitation Stretching and Ballistic Stretching on Leg Muscle Flexibility in Pencak Silat Extracurricular Participants at Kemala Bhayangkari High School. The purpose of this study was to determine the effect of Proprioseptive Neuromuscular Facilitation Stretching and Ballistic Stretching on the Flexibility of Leg Muscles in Pencak Silat Extracurricular Participants in Kemala Bhayangkari High School. The method used in this study is an experiment with True-Experimental Pretest-Postest Control Group Design research. Subjects in this study were participants who participated in pencak silat extracurricular activities at the Kemala Bhayangkari High School, totaling 26 people. Data analysis with parametric test t-test. The results of the study note that there is a significant influence on the PNF group, the value of tcount (37.60)> ttable (1.782) shows an increase in the degree of flexibility by 34%. While in the Ballistic Stretching group, the value of tcount (23.26)> ttable (1.782) shows an increase in the degree of flexibility by 17%. And in the PNF Stretching and Ballistic Stretching groups obtained tcount (5.97)> ttable (1.782) showed an increase in the degree of flexibility by 23%. From these results it can be concluded that the PNF Streching treatment has a more significant effect on leg muscle flexibility compared to Ballistic Stretching treatment. Keywords:Flexibility, Proprioseptive Neuromuscular Fasilitation, Ballistic